Observation of Tri-allelic Patterns in Autosomal STRs during Establishment of Genetic Fingerprint Database for the Iraqi Security Forces - Esam Ghazi Mohammed Salih; Mohammed Ibrahim Nader; Majeed Arsheed Sabbah; Mohammed Mahdi Al-Zubaidi; Hanan Khaleel Mahmood; Khalifah Mahdi Salih; Dhurgham Hameed Hasan (Institute of Medico-legal Publications Pvt Ltd, 2022)
We report five cases of tri-allelic patterns observed during establishment of genetic fingerprint database for 354individual from Iraqi security forces volunteers. These individuals had been typed by using the PowerPlex®Fusion System for the following 22 autosomal STRs: D3S1358, D1S1656, D2S441, D10S1248, D13S317, Penta E,D16S539, D18S51, D2S1338, CSF1PO, Penta D, TH01, vWA, D21S11, D7S820, D5S818, TPOX, D8S1179, D12S391,D19S433, FGA and D22S1045. All five tri-allelic patterns were observed at the Penta D locus and had the genotype9/11/13, 9.4/13/14, 9/10/11, 7/9/11 and 9/10/14 respectively. All cases belonged to the Type 2 tri-allelic pattern;involve a fairly balanced set of three alleles. Five cases in 354 typed individuals is a frequency for tri-allelic patternsin autosomal STRs of 1.41%.